Constructing a novel supercritical carbon dioxide power cycle with the capacity of process switching for the waste heat recovery. (26th November 2021) - Xiao, Guimin; Yu, Aofang; Lin, Xinxing; Su, Wen; Zhou, Naijun
Summary: In order to improve the utilization efficiency of fossil energy, a novel supercritical carbon dioxide (S‐CO2 ) cycle for flue gas waste heat recovery is constructed in this paper. The system can easily change the cycle processes through the switching of a triple valve. To investigate the system performances, the corresponding energy, exergy, and economy models are established. Various performances are obtained and compared with those of recompression cycle under design conditions. Thereafter, effects of key parameters on cycle performance are analyzed. In addition, according to the economic analysis, the net work is optimized to get the maximum value by genetic algorithm (GA) optimization. The results show that the proposed system has better performances than the recompression cycle. Under the optimal conditions, the net work of Process 1 and Process 2 are respectively 2912.34 and 2308.32 kW, which are 279.76 and 174.62 kW higher than the works under design conditions. Finally, the optimal performances of two processes are obtained, when the flue gas temperature varies from 250°C to 550°C. The results indicate that if the flue gas temperature is below 310°C, the net work of Process 2 is higher. Otherwise, the net work of Process 1 is higher. Thus, in the practical engineering, according to the measured flue gas temperature, the system should be switched into different processes to achieve efficient operations.